ANALISIS KELAYAKAN LOKASI TEMPAT PEMROSESAN AKHIR SAMPAH AIRMADIDI BAWAH KABUPATEN MINAHASA UTARA - Marcell Zadke Wakkary; Paulus A. Pangemanan; Leonardus Ricky Rengkung (AGRI-SOSIOEKONOMI, 2015)
Waste Treatment Location (TPA) in North Minahasa Regency need attention, because of the existing TPA has been ineffective so that will impact on the operational feasibility of the TPA. The current TPA is a reservoir of garbage from all over North Minahasa Regency. The management of waste in the TPA is only dredging and filling with the new waste. A new TPA becomes an urgency as a replacement for the old, because without the a new waste disposal location , may cause contamination. This study aimed to evaluate the feasibility of Waste Disposal Location  (TPA) in  Airmadidi Regency based on eligibility criteria of  Indonesia National Standard. The benefits of this research that it can be use as a reference for the Planning and Regional Development studies in North Minahasa Regency to determent the worthiness of the existing waste Treatment location, and can be taken into consideration for regional planning regarding the worthiness of the existing waste treatment location. Research results show that in TPA Airmadidi the level of feasibility is enough or qualified in terms with minor repairs. In the aspect of social and community perceptions  show that the level of eligibility Very Good, whereas in the physical aspects show that the aspects of waste management are at the feasibility level is less. It can be predicted that the capacity of Waste Treatment Location (TPA) in Airmadidi Regency until the end of 2025 is 458,121.9 metrics. This shows at the end of 2025 could still accommodate a charge of 8479.75 metrics with a high pile has reached 9.81 meter. It means that the existing TPA can still operate above 10 years but with less remaining operating time. However at the end of 2030, the existing TPA is already over load of 173,911.82 metrics with a height of pile 13.8 meter.